The effects of bar-spiral coupling on stellar kinematics in the galaxy - Monari, Giacomo; Famaey, Benoit; Siebert, Arnaud; Grand, Robert J. J.; Kawata, Daisuke; Boily, Christian (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. We investigate models of the Milky Way disc taking into account simultaneously the bar and a two-armed quasi-static spiral pattern. Away from major r